Poverty and food security analysis: A study of fishermen households in a selected area of Bangladesh (Journal of the Bangladesh Agricultural University, 2014)
This study examines the poverty and food security analysis of fishermen households in a selected area of Gopalganj Sadar Upazila in Gopalganj District in Bangladesh. A sample size of 60 households was selected purposively from four villages. Data was collected through field survey by using pre-designed and pre-tested questionnaire. Calorie intake levels were calculated and statistical comparisons were done. Multiple regression analysis was carried out to determine the factor influencing calorie intake in individual levels. Food consumption scores were used to determine calorie intake levels. The major findings of the study were that income, education, cultivable area and rented area had positive impact on calorie intake but age of the respondents and family size had negative impact on calorie intake. About 68.33% of the respondents belonged to hard core poor whose average calorie intake was 1692.32 k. calories and 25% of the respondents had an average calorie intake 1890.93 k. calories and they belonged to absolute poor. The rest 6.67 % of the respondents took above 2122 kilo calories and average calorie intake was 2193.50 k. calories. There was 20% households having poor food consumption and 42% having borderline food consumption. Only 6.67% fishermen households have acceptable low food consumption and 3.33% have acceptable high food consumption. DOI: http://dx.doi.org/10.3329/jbau.v11i2.19928 J. Bangladesh Agril. Univ. 11(2): 293-299, 2013